Inducible costimulator ligand (ICOSL) on CD19+ B cells is involved in immunopathological damage of rheumatoid arthritis (RA) - Ding, Sisi; Sun, Zhiyong; Jiang, Juean; Chang, Xin; Shen, Yu; Gu, Yanzheng; Liu, Cuiping (Frontiers in Immunology, 2022)
Inducible costimulator (ICOS) and its ligand (ICOSL) are critical to regulate the immune response in autoimmune diseases. The participation of B lymphocytes exhibits pathogenic potential in the disease process of rheumatoid arthritis (RA). However, the precise role of ICOSL in RA remains unclear. In this study, we aimed to explore the regulatory effects of CD19+ICOSL+ B cells in the pathogenesis of RA. We demonstrated the increased expression of ICOS and ICOSL in patients with RA and collagen-induced arthritis (CIA) mice. The population of CD19+ICOSL+ B-cell subset was significantly correlated with clinicopathological characteristics of RA patients and CIA mice. Adoptive transfer of CD19+ICOSL+ B cells aggravated arthritic progression in CIA mice. Moreover, microarray analysis revealed that CD19+ICOSL+ cells could exert pivotal effect in pathological process of RA. Further blocking of ICOSL significantly inhibited proinflammatory responses and ameliorated arthritic progression. Therefore, CD19+ICOSL+ B-cell subset could be defined as a specific pathogenic cell subpopulation involved in immunopathological damage of RA. Blockade of ICOSL is promising to be a potential new approach for RA therapy.